Differential Contribution of Lipoxygenase Isozymes to Nigrostriatal Vulnerability - Chou, Vivian P. (Neuroscience, 2012)
The 5- and 12/15- lipoxygenase (LOX) isozymes have been implicated to contribute to disease development in CNS disorders such as Alzheimer's disease. These LOX isozymes are distinct in function, with differential effects on neuroinflammation, and the impact of the distinct isozymes in the pathogenesis of Parkinson's disease (PD) has not as yet been evaluated. To determine whether the isozymes contribute differently to nigrostriatal vulnerability, the effects of 5- and 12/15-LOX deficiency on dopaminergic tone under na ve and toxicant-challenged conditions were tested. In na ve mice deficient in 5-LOX expression, a modest but significant reduction (18.0% reduction vs. wildtype (WT)) in striatal dopamine (DA) was detected (n=6-8 per genotype). A concomitant decline in striatal tyrosine hydroxylase (TH) enzyme was also revealed in null 5-LOX vs. WT mice (26.2%); however, no changes in levels of DA or TH immunoreactivity were observed in null 12/15-LOX vs. WT mice. When challenged with the selective dopaminergic toxin, 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP), WT mice showed marked reduction in DA (31.9%) and robust astrocytic and microglial activation as compared to saline-treated animals. In contrast, null 5-LOX littermates demonstrated no significant striatal DA depletion or astrogliosis (as noted by Western blot analyses for GFAP immunoreactivity). In na ve null 12/15-LOX mice, no significant change in striatal DA values was observed compared to WT, and following MPTP treatment, the transgenics revealed striatal DA reduction similar to the challenged WT mice. Taken together, these data provide the first evidence that: (i) LOX isozymes are involved in the maintenance of normal dopaminergic function in the striatum, and (ii) the 5- and 12/15-LOX isozymes contribute differentially to striatal vulnerability in response to neurotoxicant challenge.